MANAJEMEN VIRTUAL OFFICE BERBASIS PLATFORM DIGITAL DI PERUSAHAAN GRAB BENGKULU - Lathifatul Ainy; Sugeng Suharto; Gushevinalti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of digital platform-based virtual office management at Grab Bengkulu and identify how digital platforms support management functions, including planning, organizing, directing, and controlling (POAC). This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation involving management and employees engaged in the virtual work system at Grab Bengkulu. The findings indicate that the implementation of virtual offices is supported by various digital platforms such as WhatsApp, Zoom Meetings, Google Drive, and the company’s internal operational system. These platforms facilitate work coordination, communication, decision-making, performance monitoring, and human resource management in an online environment. The planning function is implemented through digitally based work targets and flexible operational strategies. The organizing function is reflected in structured task distribution and virtual coordination. The directing function is carried out through digital leadership and intensive online communication, while the controlling function is implemented through data-based evaluation systems and real-time performance monitoring. This study concludes that digital platform-based virtual office management improves work flexibility, coordination effectiveness, and organizational operational efficiency, although challenges remain in maintaining communication, work discipline, and employee supervision in a virtual work environment.